2014
DOI: 10.1007/s10886-014-0489-y
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analyses of Courtship Pheromones in the Redback Salamander, Plethodon cinereus

Abstract: The evolutionary success of plethodontid salamanders for ~100 MY is due partly to the use of courtship pheromones that regulate female receptivity. In ~90 % of plethodontid species, males deliver pheromones by "scratching" a female's dorsum, where pheromones diffuse transdermally into the bloodstream. However, in a single clade, representing ~10 % of Plethodon spp., males apply pheromones to the female's nares for olfactory delivery. Molecular studies have identified three major pheromone families: Plethodonti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 48 publications
1
24
0
Order By: Relevance
“…In all molecular and proteomic studies to date, we have demonstrated recruitment and co-option of multiple gene families followed by rapid evolution [23,25,26,28,44]. Specifically, our proteomic studies demonstrate large changes in pheromone composition between genera, even for those using the same delivery mode [28,45]. A key question remains is what factors allow a gene to be coopted.…”
Section: Recruitment Of Novel Pheromone Families By Gene Co-optionmentioning
confidence: 79%
See 1 more Smart Citation
“…In all molecular and proteomic studies to date, we have demonstrated recruitment and co-option of multiple gene families followed by rapid evolution [23,25,26,28,44]. Specifically, our proteomic studies demonstrate large changes in pheromone composition between genera, even for those using the same delivery mode [28,45]. A key question remains is what factors allow a gene to be coopted.…”
Section: Recruitment Of Novel Pheromone Families By Gene Co-optionmentioning
confidence: 79%
“…Recent proteomic analyses in the redback salamander (Plethodon cinereus) revealed that, despite using the transdermal mode of delivery, its pheromone composition was principally composed of PRF and PMF, similar to that of P. shermani (which uses slapping delivery) [28].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Initial pheromone characterization was performed for P. shermani using multiple types of high performance liquid chromatography (HPLC) to isolate individual proteins, which were then identified by MS analysis using a shotgun EST library as a reference [109,110]. Subsequent studies with D. ocoee and P. cinereus instead used de novo transcriptomes as reference databases, with amplification of identified candidates by RT-PCR and validation by Sanger sequencing [111,112]. Despite detection of SPF mRNA by RT-PCR in all three species, it was only observed proteomically in D. ocoee , where it comprised ∼30% of the total pheromone.…”
Section: Protein Pheromones In Vertebratesmentioning
confidence: 99%
“…First, PRF was heavily glycosylated in P. cinereus and not P. shermani , with the loss of glycosylation resulting from mutation of two NXS/NXT N-glycosylation motifs and an alternative signal peptidase cleavage position which removes an O-glycan near the N-terminus. While glycosylation can affect various aspects of protein solubility, stability, and receptor specificity, its functional significance in this pheromone context remains to be determined [111]. Second, P. shermani expresses ∼5–10 times more PMF isoforms compared to P. cinereus (Fig.…”
Section: Protein Pheromones In Vertebratesmentioning
confidence: 99%
“…Little is known on how protein pheromone blends evolve species‐specific effects and how sexual selection shapes protein pheromone evolution (Gomez‐Diaz & Benton, ; Peterson et al., ; Touhara, ; Wyatt, ,). Although recombination, alternative splicing and glycosylation can add a source of variation on top of the existing protein variation (Janssenswillen, Vandebergh, et al., ; Van Bocxlaer et al., ; Wilburn et al., ), there are essentially two ways to evolve species specificity for a given multiprotein pheromone system. On the one hand, each of the proteins themselves can evolve through the process of random mutation, selection or drift, leading to sequence divergence (Lemey, Salemi, & Vandamme, ), which can potentially change their shape and consequent interactions with receptors (Nakada et al., ; Wyatt, ; Yamamoto et al., ).…”
Section: Introductionmentioning
confidence: 99%